Diet affordability: Understanding the high cost of healthy diets - Headey, Derek D.; Hirvonen, Kalle; Alderman, Harold; de Pee, Saskia; Raghunathan, Kalyani (International Food Policy Research Institute, 2024)
As new metrics of healthy diet affordability have been developed in the past five years, it is estimated that between 2 and 3 billion people worldwide — mostly in low- and middle-income countries (LMICs) — cannot afford a healthy diet. The implications for human nutrition are striking: affordability is a binding constraint to achieving a healthy diet in the world’s poorest countries. This chapter poses several questions to initiate strategic thinking on possible responses to this challenge and recommends actions to support shifts toward healthy diets in LMICs.